Тhe trends of militarization of the foreign and regional policy of modern Turkey - Hovsepyan, Levon; Petrosyan, Armen (YSU Journal of International Affairs, 2021)
Turkish current foreign and regional policy characterised as militaristic and oversecuritized, is being accompanied with the nationalistic and irredentist official rhetorics, which tends to revise the status-quo in the neighbouring regions. The article analyses the intensive use of military power in regional policy, the strategy based on the military interventions and proxy wars in the neighbouring regions and countries. Theoretical and academic approaches on the militarization and securitization of the Turkish foreign and regional policy and the influence of external and domestic factors on it were also viewed. Turkish military interventions and proxy wars in Syria, Libya, Iraq, provocative and aggresive behavour in the Eastern Mediterranian were observed. As a continuation of Turkish revisionism and interventionism, the South Caucasus became the next target of Turkish ambitions, when in 2020 Turkish-Azerbaijani tandem, with the involvement of foreign jihadist fighters, launched a full-scale war against Nagorno-Karabakh Republic.
Keywords: Turkey; foreign policy; regional conflict; militarization; securitization; revisionism